Persepsi Suami Mengenai Webseries Layangan Putus : Sebuah Tinjauan Efek Komunikasi - Widuhung, Selvy Maria (Brand Communication, 2023)
Marriage is a very important thing in life. There are many marriages fail because the partners is unfaithful or having an affair. The existence of the Layangan Putus Webseries has provided lessons for wives on how to deal with infidelity in their households. However, it also gives a perception from the husbands regarding the fidelity perspective from their side. This will be discussed scientifically by looking at the communication effects of the Disconnected Kite web series in a cognitive, affective and behavioral way. The research method used is qualitative with data collection through Forum Group Discussion (FGD), to five sources with predetermined criteria. At the end of this study it will be seen that husbands are also affected Cognitively, Affectively and Behaviorally which can be seen from their perceptions of how to maintain fidelity so that their marriage can last a long time.